# |
ODE |
Mathematica |
Maple |
\[
{}x^{\prime \prime }+x = \sin \left (t \right )-\cos \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y^{\prime \prime \prime }-3 y^{\prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \frac {1}{\sin \left (x \right )^{3}}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-4 x y^{\prime }+6 y = 2
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \cosh \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+\frac {2 {y^{\prime }}^{2}}{1-y} = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-4 x^{\prime }+4 x = {\mathrm e}^{t}+{\mathrm e}^{2 t}+1
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }+{y^{\prime }}^{2}+1 = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} x^{\prime \prime }+1 = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-16 y = x^{2}-{\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}{y^{\prime \prime \prime }}^{2}+{y^{\prime \prime }}^{2} = 1
\] |
✓ |
✓ |
|
\[
{}x^{\left (6\right )}-x^{\prime \prime \prime \prime } = 1
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime \prime \prime }-2 x^{\prime \prime }+x = t^{2}-3
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 x y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+\left (9 x^{2}-\frac {1}{25}\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+{y^{\prime }}^{2} = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = 3 \sqrt {y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = 1-\frac {1}{\sin \left (x \right )}
\] |
✓ |
✓ |
|
\[
{}u^{\prime \prime }+\frac {2 u^{\prime }}{r} = 0
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime }+{y^{\prime }}^{2} = \frac {y y^{\prime }}{\sqrt {x^{2}+1}}
\] |
✓ |
✓ |
|
\[
{}y y^{\prime } y^{\prime \prime } = {y^{\prime }}^{3}+{y^{\prime \prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+9 x = t \sin \left (3 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+y = \sinh \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-y = {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+2 y = x \,{\mathrm e}^{x} \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-1\right ) y^{\prime \prime }-6 y = 1
\] |
✓ |
✓ |
|
\[
{}m x^{\prime \prime } = f \left (x\right )
\] |
✓ |
✓ |
|
\[
{}m x^{\prime \prime } = f \left (x^{\prime }\right )
\] |
✓ |
✓ |
|
\[
{}y^{\left (6\right )}-3 y^{\left (5\right )}+3 y^{\prime \prime \prime \prime }-y^{\prime \prime \prime } = x
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime \prime \prime }+2 x^{\prime \prime }+x = \cos \left (t \right )
\] |
✓ |
✓ |
|
\[
{}\left (1+x \right )^{2} y^{\prime \prime }+\left (1+x \right ) y^{\prime }+y = 2 \cos \left (\ln \left (1+x \right )\right )
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime }-x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime \prime \prime }+x = t^{3}
\] |
✓ |
✓ |
|
\[
{}{y^{\prime \prime }}^{3}+y^{\prime \prime }+1 = x
\] |
✗ |
✓ |
|
\[
{}x^{\prime \prime }+10 x^{\prime }+25 x = 2^{t}+t \,{\mathrm e}^{-5 t}
\] |
✓ |
✓ |
|
\[
{}x y y^{\prime \prime }-x {y^{\prime }}^{2}-y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\left (6\right )}-y = {\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\left (6\right )}+2 y^{\prime \prime \prime \prime }+y^{\prime \prime } = x +{\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}6 y^{\prime \prime } y^{\prime \prime \prime \prime }-5 {y^{\prime \prime \prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime } = y^{\prime } \ln \left (\frac {y^{\prime }}{x}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \sin \left (3 x \right ) \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = 2 y^{3}
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime }-{y^{\prime }}^{2} = y^{\prime }
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = y \left (t \right ), y^{\prime }\left (t \right ) = -x \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right )+5 x \left (t \right )+y \left (t \right ) = {\mathrm e}^{t}, y^{\prime }\left (t \right )-x \left (t \right )-3 y \left (t \right ) = {\mathrm e}^{2 t}]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = y \left (t \right ), y^{\prime }\left (t \right ) = z \left (t \right ), z^{\prime }\left (t \right ) = x \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}\left [x^{\prime }\left (t \right ) = y \left (t \right ), y^{\prime }\left (t \right ) = \frac {y \left (t \right )^{2}}{x \left (t \right )}\right ]
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y \,{\mathrm e}^{x +y} \left (x^{2}+1\right )
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime } = 1+y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (x y\right )
\] |
✗ |
✗ |
|
\[
{}x \left ({\mathrm e}^{y}+4\right ) = {\mathrm e}^{x +y} y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \cos \left (x +y\right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = x y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = t \ln \left (y^{2 t}\right )+t^{2}
\] |
✓ |
✗ |
|
\[
{}y^{\prime } = x \,{\mathrm e}^{y^{2}-x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \ln \left (x y\right )
\] |
✗ |
✗ |
|
\[
{}x \left (1+y\right )^{2} = \left (x^{2}+1\right ) y \,{\mathrm e}^{y} y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+x^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+x y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}y^{\left (5\right )}-y^{\prime \prime \prime \prime }+y^{\prime } = 2 x^{2}+3
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y y^{\prime \prime \prime \prime } = 1
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime \prime }+x y = \cosh \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } \cos \left (x \right )+y \,{\mathrm e}^{x^{2}} = \sinh \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+x y = \cosh \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}\sinh \left (x \right ) {y^{\prime }}^{2}+3 y = 0
\] |
✓ |
✓ |
|
\[
{}5 y^{\prime }-x y = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2} \sqrt {y} = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime }+3 y^{\prime }+4 x^{2} y = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime } = 1
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-y = \sin \left (x \right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = x^{2}+y
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+x y^{\prime \prime }-y^{2} = \sin \left (x \right )
\] |
✗ |
✗ |
|
\[
{}{y^{\prime }}^{2}+x y {y^{\prime }}^{2} = \ln \left (x \right )
\] |
✗ |
✗ |
|
\[
{}\sin \left (y^{\prime \prime }\right )+y y^{\prime \prime \prime \prime } = 1
\] |
✗ |
✗ |
|
\[
{}\sinh \left (x \right ) {y^{\prime }}^{2}+y^{\prime \prime } = x y
\] |
✗ |
✗ |
|
\[
{}y y^{\prime \prime } = 1
\] |
✓ |
✓ |
|
\[
{}{y^{\prime \prime \prime }}^{2}+\sqrt {y} = \sin \left (x \right )
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-5 y^{\prime \prime }+y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime }-3 y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}3 y^{\prime \prime \prime \prime }-2 y^{\prime \prime }+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (x -3\right ) y^{\prime \prime }+y \ln \left (x \right ) = x^{2}
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime }+\tan \left (x \right ) y^{\prime }+y \cot \left (x \right ) = 0
\] |
✗ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }+\left (x -1\right ) y^{\prime }+y = 0
\] |
✗ |
✓ |
|
\[
{}x y^{\prime \prime }+2 x^{2} y^{\prime }+y \sin \left (x \right ) = \sinh \left (x \right )
\] |
✗ |
✗ |
|
\[
{}\sin \left (x \right ) y^{\prime \prime }+x y^{\prime }+7 y = 1
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime }-\left (x -1\right ) y^{\prime }+x^{2} y = \tan \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\left (x -1\right ) y^{\prime \prime }-x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-4 x^{2} y^{\prime }+\left (x^{2}+1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+\frac {k x}{y^{4}} = 0
\] |
✗ |
✓ |
|
\[
{}y^{\prime \prime }+2 x y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+\sin \left (x \right ) y^{\prime }+y \cos \left (x \right ) = 0
\] |
✗ |
✓ |
|
\[
{}y^{\prime \prime }+2 x^{2} y^{\prime }+4 x y = 2 x
\] |
✓ |
✓ |
|
\[
{}\left (-x^{2}+1\right ) y^{\prime \prime }+\left (1-x \right ) y^{\prime }+y = 1-2 x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 x y^{\prime }+\left (4 x^{2}+2\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x^{2} y^{\prime }+2 \left (1-x \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+x^{2} y^{\prime }+2 x y = 2 x
\] |
✓ |
✓ |
|
\[
{}\ln \left (x^{2}+1\right ) y^{\prime \prime }+\frac {4 x y^{\prime }}{x^{2}+1}+\frac {\left (-x^{2}+1\right ) y}{\left (x^{2}+1\right )^{2}} = 0
\] |
✗ |
✗ |
|